Feasibility and acceptability of nationwide HPV vaccine introduction in Senegal: Findings from community-level cross-sectional surveys, 2020 - Reena H. Doshi; Rebecca M. Casey; Nedghie Adrien; Alassane Ndiaye; Timothy Brennan; Jerlie Loko Roka; Awa Bathily; Cathy Ndiaye; Anyie Li; Julie Garon; Ousseynou Badiane; Aliou Diallo; et al. (Public Library of Science (PLoS), 2022)
In Senegal, cervical cancer is the most common cancer among women and the leading cause of morbidity and mortality from all cancers. In 2018, Senegal launched a national human papillomavirus (HPV) vaccination program with Gavi, the Vaccine Alliance (Gavi), support. HPV vaccination was incorporated into the national immunization program as a two-dose schedule, with a 6-12-month interval, to nine-year-old girls via routine immunization (RI) services at health facilities, schools and community outreach services throughout the year. During February to March 2020, we conducted interviews to assess the awareness, feasibility, and acceptability of the HPV vaccination program with a cross-sectional convenience sample of healthcare workers (HCWs), school personnel, community healthcare workers (cHCWs), parents, and community leaders from 77 rural and urban health facility catchment areas. Participants were asked questions on HPV vaccine knowledge, delivery, training, and community acceptability of the program. We conducted a descriptive analysis stratified by respondent type. Data were collected from 465 individuals: 77 HCW, 78 school personnel, 78 cHCWs, 152 parents, and community leaders. The majority of HCWs (83.1%) and cHCWs (74.4%) and school personnel (57.7%) attended a training on HPV vaccine before program launch. Of all respondents, most (52.5-87.2%) were able to correctly identify the target population. The majority of respondents (60.2-77.5%) felt that the vaccine was very accepted or accepted in the community. Senegal's HPV vaccine introduction program, among the first national programs in the African region, was accepted by community stakeholders. Training rates were high, and most respondents identified the target population correctly. However, continued technical support is needed for the integration of HPV vaccination as a RI activity for this non-traditional age group. The Senegal experience can be a useful resource for countries planning to introduce the HPV vaccine.